THE CONNECTION BETWEEN ENVIRONMENT AND ARCHITECTURE IS AN IMPORTANT COMPONENT OF THE OBJECTS - Журавська, Наталія; Лапінський, С.В. (SWorldJournal, 2024)
Integrating ecological principles into architecture is necessary to ensure sustainable development and preserve the environment for future generations. The main principles of ecological architecture are energy efficiency, use of renewable resources, reduc